City Water Resilience Framework: A governance based planning tool to enhance urban water resilience. (February 2022) - Saikia, Panchali; Beane, George; Garriga, Ricard Giné; Avello, Pilar; Ellis, Louise; Fisher, Sophie; Leten, James; Ruiz-Apilánez, Iñigo; Shouler, Martin; Ward, Robin; Jiménez, Alejandro
Highlights: The ability to manage and build urban water resilience will depend on how the city is managing and governing its water resources and services and how it is addressing the water-related shocks and stresses There is an increasing demand for innovative tools and guidance to apply water resilience concept in practice. With empirical evidence, the paper presents a water resilience assessment framework that includes a set of resilience indicators that will guide in building urban water resilience Critical dimensions to build urban water resilience: infrastructure and ecosystems, health and wellbeing, planning and finance, and leadership and strategy. Abstract: The resilience model is an increasingly well-established paradigm of urban planning that guides responses to water related shocks and stresses, such as floods, droughts. However, due to limited studies and guidance on how to apply the concept of water resilience in practice, there is a growing demand for innovative tools that can help urban planners make better decisions and investments for a resilient urban water system. This paper presents a governance-based water resilience planning tool called the City Water Resilience Framework (CWRF), which is designed to meet this need. CWRF enables cities to collectively assess and plan for strengthening urban water resilience. It has been co-created through research and a robust peer-review process with eight partner cities and consultation with global experts. Based on this research, different factors of resilience were identified, which informed the development of CWRF, that includes a set of resilience goals, sub-goals and indicators, categorised across four dimensions: infrastructure and ecosystems, health and wellbeing, planning and finance, and leadership and strategy. Evidence is presented from the application of CWRF in Cape Town and Greater Miami and the Beaches (GM&B), which informed the cities' key water planning and strategies by integrating water resilience factors and activities.